Self-perception of oral health in elderly with acrylic removable partial acrylic prosthesis - Marcilia Rodríguez Fuentes; Yunier Arpajón Peña; Isis Bárbara Herrera López; Milay Justo Díaz; Zuilen Jiménez Quintana (Editorial Ciencias Médicas, 2017)
Introduction: the increase of the number of older people leads to an increase in the number of people going to the dental services looking for rehabilitation, and in most of cases, they do not adapt themselves to the new conditions. Objective: to identify the association of some factors that influence in the self-perception of oral health over the older adults with removable acrylic partial denture. Methods: observational and descriptive research study conducted in 150 randomly selected old people aged over 60 years with denture. The evaluation variables were age, sex, type of denture, schooling, previous experience and length of wear, in association with self-perception of oral health measured by the geriatric oral health assessment index. Results: fifty three percent of patients were 60 to 69 years-old and this age group exhibited the most frequent regular self-perception (49.3 %). Males (16 %) were the ones with more frequency of responses that agreed with good self-perception. The highest frequency of bad self-perception was found in high school and university students who together accounted for 19 %, in persons wearing upper denture (17.3 %) and in those with previous experience of denture (25 %). Twenty four percent of the group had been orally rehabilitated for 4 years or more with bad self-perception of oral health. Conclusions: less than 80 years of age, masculine sex, denture rehabilitation in both dental arches and previous experiences of wearing dentures are the factors that mostly relate to good self-perception of oral health in older adults.